Faktor-Faktor yang Berhubungan dengan Kejadian Partus Lama pada Ibu Bersalin di RSUD Djoelham Binjai Tahun 2023 - Galuh Pravita Sari Sembiring; Erin Padilla Siregar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
The maternal mortality rate (MMR) in the world based on data from the World Health Organization, according to the World Health Organization (WHO), in 2016 reached 289,000 people, divided into several countries, including the United States reaching 9,300 people, North Africa 179,000 people and Southeast Asia 16,000 soul. Approximately 80% of maternal deaths are the result of increased complications during pregnancy, childbirth and after delivery. Causes of maternal death include postpartum hemorrhage, eclampsia, prolonged labor and sepsis. One of the causes of maternal death is prolonged labor with an average number in the world of 8% and in Indonesia it is 9%. The general aim of this research is to determine the factors associated with the incidence of prolonged labor in women giving birth at the Djoelham Binjai Regional Hospital in 2023. Prolonged labor is a situation where the latent phase occurs for more than 8 hours or labor lasts more than 12 hours with the baby not yet being born. On a partograph, labor that is not progressing is indicated by cervical dilatation above the alert line (right side) in the active phase. The pathophysiology of prolonged labor is closely related to the concept of functional stages of labor which explains the physiological goals of labor. There are three functional stages of labor, namely the preparatory division, the opening/dilatation stage and the pelvic division. This research uses a quantitative type of research using retrospective research. The design of this research was carried out using a cross sectional approach. The sample in the study was women giving birth who experienced a long labor at Djoelham Binjai Regional Hospital in 2023. The proportion of respondents who had a long labor due to a weak vagina < 20' was 12 (40%), respondents who had a long labor due to CPD with In the No CPD category, there were 13 (43.3%) respondents who did not give birth for a long time due to their weight, with the weight category > 4000 grams being 12 (40%). The results (p value = 0.030 < 0.05) which means that this research shows that there is a significant relationship between His, CPD and Baby's Weight with Long Parturition at Djoelham Binjai Regional Hospital. The strength and weakness of the His during the birth process greatly influences the speed or Length of labor It is hoped that respondents will be more active in checking their pregnancies to avoid prolonged labor by health workers either at posyandu or other health service places. Keywords: Partus Lama, Persalinan